Seasonal Effects of Extreme Weather Events on Potential Extracellular Enzyme Activities in a Temperate Grassland Soil - Hammerl, Verena B.; Grant, Kerstin; Pritsch, Karin; Jentsch, Anke; Schloter, Michael; Beierkuhnlein, Carl; Gschwendtner, Silvia (Frontiers in Environmental Science, 2019)
Magnitude and timing of precipitation events within the growing season might be decisive for alterations in potential extracellular enzyme activity (PEEA), with consequences for nutrient cycle, and carbon storage in grassland ecosystems. Pattern of PEEA catalyzing major steps of the carbon cycle (β-glucosidase (β-gls), cellobiohydrolase (cel), glucuronidase (glr), and xylosidase (xyl), soil respiration rates and extractable organic carbon were analyzed in response to increased intra-annual precipitation variability in a European, mesic temperate grassland. The field experiment was carried out in three subsequent years by simulating recurrent drought events combined with heavy rainfall either early or late in the growing season (spring or summer) by rainout shelters and irrigation systems. Our data indicated comparable effects of the drought settings independent from the timing of the drought. Both for the simulated spring- and summer drought a decrease of enzymatic activities was observed compared to the control plots, with ß-gls activity after the summer drought being the only exception. However, response pattern toward rewetting differed depending on the seasonal timing of the drought being introduced. After spring drought, a fast recovery to control level was observed for PEEA of ß-gls and xyl, whereas cel and glr activity remained constantly lower. Rewetting after summer drought induced an increase of all enzymatic activities to values even higher compared to the controls. Overall, our data indicate a high resilience of PEEA toward drought and rewetting events in grassland soils, which is modulated by the seasonal timing of the extreme weather events.